a)3π pe 4=π-π pe4=cosπ pe4=sinπ pe4=radical din2 pe 2
5π pe 4=2π-π pe 4=sinπ pe 4=cosπ pe 4=radical din2 pe 2
7π pe 4=2π+π pe 4=sinπ pe 4=cosπ pe 4=radical din2 pe 2
b)2π pe 3=π-π pe 3=sinπ pe 3=radical din 3 pe 2
=cos π pe 3=1 pe 2
4π pe 3=π+π pe 3=sinπ pe 3=radical din 3 pe 2
=cos π pe 3=1 pe 2
5π pe 3=2π-π pe 3 =sin π pe 3=radical din 3 pe 2
=cos π pe 3=1 pe 2
c)5π pe 6=π-π pe 6=sin π pe 6=1 pe 2
=cos π pe 6=radical din 3 pe 2
7π pe 6=π+π pe 6=sin π pe 6=1 pe 2
=cos π pe 6=radical din 3 pe 2
11π pe 6=2π-π pe=sin π pe 6=1 pe 2
=cos π pe 6=radical din 3 pe 2